Relapse of both small cell lung cancer and Lambert–Eaton myasthenic syndrome after a 13-year disease-free survival period. Issue 1 (December 2016) - Asano, Fumio; Watanabe, Keisuke; Shinkai, Masaharu; Tei, Yoshitaka; Mishina, Kei; Tanabe, Mikiko; Ishii, Hiroshi; Shinoda, Masahiro; Shimokawaji, Tadasuke; Kudo, Makoto; Kaneko, Takeshi
Abstract Lambert–Eaton myasthenic syndrome (LEMS) is a paraneoplastic syndrome and only 3% of small cell lung carcinoma (SCLC) patients have LEMS. Moreover, the recurrence of SCLC after a disease-free survival (DFS) of more than 10 years is rare. We report a patient who had a recurrence of both SCLC and LEMS after a 13-year DFS period. A 69-year-old man was diagnosed with LEMS and SCLC (cT0N2M0, stage IIIA) 13 years ago. Chemoradiotherapy was performed and a complete response was achieved. With anticancer treatment, the LEMS symptoms was alleviated. At the age of 82 years, gait disturbance appeared followed by left supraclavicular lymphadenopathy and further examination revealed the recurrence of SCLC. Careful screening for the recurrence of SCLC might be needed when the patient has recurrent or secondary paraneoplastic neurological syndrome even after a long DFS period.